(untitled) (Oxford, 2015)
Those with an interest in classical language and literature, ancient history, Roman art, political and economic systems, or the concept of civilization as a whole, will gain a greater understanding of both the Romans and the model of a civilization that has shaped so many cultures.
Keywords: Người La Mã,Romans